Research on carbon emission potential of electric vehicles and fuel vehicles - Zhou Qiang; Liu Wanfu; Qi Wuqin (E3S Web of Conferences, 2021)
Electric vehicles are considered as a effective tool for energy conservation and emission reduction, Because of its zero direct carbon emissions. However, thermal power generation accounts for a large proportion in China's power generation structure, so the indirect carbon emissions of electric vehicles must be considered. In order to further study the carbon emission potential of electric vehicles compared with traditional fuel vehicles, the direct carbon emission of fuel vehicles and the indirect carbon emission of battery electric vehicles were calculated. The results show that the carbon reduction effect of electric vehicles is obvious, and the coal power technology and the energy structure of power generation have great influence on the carbon reduction potential of electric vehicles. Based on this, suggestions are put forward to promote electric vehicles and fully release their emission reduction potential from the aspects of enhancing consumers' perception of social value, improving energy structure and improving coal power technology.